Youth mental health competencies in regional general practice. (April 2021) - Smith, Oliver; Bergmann, Jessica; Schall, Ulrich
Objective: General practitioners (GPs) are key health professionals for referrals to mental health specialists. Youth mental health issues are particularly challenging, requiring a competent assessment and understanding of appropriate referral pathways. We surveyed local GPs about their understanding of youth mental health problems and needs to competently look after young patients. Methods: GPs working in the Hunter region were contacted via email, fax and post over a 6-month period in 2019. Results: Seventy-five GPs participated. They reported 577 of 1698 (34%) of young people seen 2 weeks prior to being surveyed presented with a mental health problem. Predominantly, referrals were to private practice psychologists and Headspace. Almost a third (31%) reported having limited understanding of 'at-risk mental state' and are 'not always comfortable' when facing a young person with a mental health problem. Nearly all (95%) expressed interest in attending specialised training. GPs identified treatment costs, scarce access to psychiatrists and limited patient engagement as the main obstacles to help young people. Conclusions: Effective treatment of a mental health problem relies on early identification. GPs are seeing young people on a regular basis but don't feel well equipped for this task and are keen to up-skill, which needs to be addressed by targeted training.